On some properties of solutions of quasilinear degenerate equations - Amanov, R. A.; Mamedov, F. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
For the quasilinear equations div A(x, u, ∇u) = 0 with degeneracy ω(x) from the Muckenhaupt Ap -class, we prove the Harnack inequality, an estimate of the Holder norm, and a sufficient test for the regularity of boundary points of the Wiener type.